Exchange Rate, Dividend Policy, and Capital Structure: Their Impact on Stock Returns in Jakarta Islamic Index Companies (2019–2023) - Maulidha, Afisa Nur; Sari, Pristin Prima; Damanik, Johannes Maysan (Dinasti Publisher, 2025)
This study aims to analyze the impact of exchange rates, dividend policies, and capital structures on stock returns of JII-listed companies from 2019-2023, considering unique characteristics and adherence to Sharia principles. This study uses a qualitative method, employing purposive sampling techniques to determine the sample and then analyzing it using multiple linear regression with the SPSS 25.0 application. The sample in this study consists of 23 companies listed on the IDX that are included in the JII index and are non-bank companies. The results of this study found that the exchange rate has a positive effect on stock return. Dividend policy, measured using the dividend payout ratio (DPR), has a negative and significant effect on stock return. Capital structure, measured using the debt to equity ratio (DER), has a negative and significant effect on stock return. Meanwhile, simultaneously, the variables of exchange rates, dividend policies, and capital structures have a significant effect on stock return. The findings provide valuable insights for investors and companies seeking to make informed investment decisions and develop effective financial strategies aligned with Sharia principles. The study contributes academically to sharia-based finance literature and offers practical implications for market participants in the Islamic capital market.